2020
DOI: 10.1074/jbc.ra120.015685
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural characterization of allosteric activation of phospholipase Cε by Rap1A

Abstract: Phospholipase Cε (PLCe) is activated downstream of G protein-coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs) through direct interactions with small GTPases, including Rap1A and Ras. While Ras has been reported to allosterically activate the lipase, it is not known whether Rap1A has the same ability, or what its molecular mechanism might be. Rap1A activates PLCε in response to the stimulation of β-adrenergic receptors (β-ARs), translocating the complex to the perinuclear m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Our studies with TSHR are consistent with Ca 2+ as the main intracellular factor regulating nuclear sAC-dependent cAMP accumulation using a Gαq-independent PLC-InsP3-InsP3R pathway. Among the PLC isoforms, a likely candidate is PLCε, a GPCR-activated isoform that is modulated by Rap1-GTP, that binds directly to and allosterically modulates PLCε ( 87 ), but not Gαq ( 88 , 89 ). Furthermore, it was reported that PLCε resides in perinuclear membranes near the nuclear envelope ( 90 , 91 ) and has previously been shown to mediate Epac1-Rap1 stimulatory effects on InsP3 production and Ca 2+ release ( 92 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies with TSHR are consistent with Ca 2+ as the main intracellular factor regulating nuclear sAC-dependent cAMP accumulation using a Gαq-independent PLC-InsP3-InsP3R pathway. Among the PLC isoforms, a likely candidate is PLCε, a GPCR-activated isoform that is modulated by Rap1-GTP, that binds directly to and allosterically modulates PLCε ( 87 ), but not Gαq ( 88 , 89 ). Furthermore, it was reported that PLCε resides in perinuclear membranes near the nuclear envelope ( 90 , 91 ) and has previously been shown to mediate Epac1-Rap1 stimulatory effects on InsP3 production and Ca 2+ release ( 92 95 ).…”
Section: Discussionmentioning
confidence: 99%